EFFECT OF DIFFERENT SOURCES AND LEVELS OF BORON ON GROWTH AND YIELD OF TOMATO (Solanum lycopersicum - ALTAF KUNTOJI; C. T. SUBBARAYAPPA (The Bioscan, 2021)
A field experiment was conducted during 2016-17 on sandy loam soil at Nayanhalli village, Chintamani taluk, Chickaballapura district, Karnataka to study the effect of different sources (borax, boric acid and boron metalosate) and levels of boron on growth and yield of tomato (Solanum lycopersicum). The results of the experiment showed that treatment receiving recommended doses of NPK+FYM + 1.1 kg B ha -1 through borax as soil application + 0.05 per cent B through boron metalosate as foliar application recorded significantly higher plant height (105.01 and 126.76 cm), number of branches per plant (7.50 and 8.57) and chlorophyll content (39.23 and 33.45) at 60 and 90 days after transplanting of tomato. Similarly, significant increase in the yield parameters such as number of fruits per plant (40.33), ten fruit weight (865.67 g), fruit yield per plant (3.12 kg), fruit yield per plot (78.04 kg) and fruit yield (57.80 t ha -1 ) were recorded highest in the treatment receiving 1.1 kg ha -1 B through soil and foliar application of 0.05 per cent boron metalosate along with recommended doses of NPK+FYM. Conclusively, combination of soil and foliar application of boron has got advantageous over only soil application of boron.